Redox Potential Heterogeneity in Fixed‐Bed Electrodes Leads to Microbial Stratification and Inhomogeneous Performance. Issue 4 (19th January 2021) - Quejigo, Jose Rodrigo; Korth, Benjamin; Kuchenbuch, Anne; Harnisch, Falk
Abstract: Bed electrodes provide high electrode area‐to‐volume ratios represent a promising configuration for transferring bioelectrochemical systems close to industrial applications. Nevertheless, the intrinsic electrical resistance leads to poor polarization behavior. Therefore, the distribution of Geobacter spp. and their electrochemical performance within exemplary fixed‐bed electrodes are investigated. A minimally invasive sampling system allows characterization of granules from different spatial locations of bed electrodes. Cyclic voltammetry of single granules ( n =63) demonstrates that the major share of electroactivity (134.3 mA L −1 ) is achieved by approximately 10 % of the bed volume, specifically that being close to the current collector. Nevertheless, analysis of the microbial community reveals that Geobacter spp. dominated all sampled granules. These findings clearly demonstrate the need for engineered bed electrodes to improve electron exchange between microorganisms and granules. Abstract : Not all spots are equally cozy : As revealed by electrochemical and microbial analysis, there is strong redox stratification in fixed‐bed electrodes, leading to a preference of Geobacter spp. to zones close to the current collector. Consequently, Geobacter spp. and its electrochemical performance are not uniformly distributed throughout the bed electrode.